Предмет: Алгебра, автор: Miralina05

решите уравнение f(x+2)=f(x-2)+4, если f(x)=3+2x+x^2

Ответы

Автор ответа: gig1007001
0

3 + 2x + 4 +{x}^{2}  + 4x + 4 = 3 + 2x - 4 +  {x}^{2}  - 4x + 4 + 4
8x =  - 4
x =  - 0.5
Автор ответа: snow99
0

f(x) = 3 + 2x +  {x}^{2}  \\ f(x + 2) = 3 + 2(x + 2) +  {(x + 2)}^{2}  = 3 + 2x + 4 +  {x}^{2}  + 4x + 4 =  {x}^{2}  + 6x + 11  \\ f(x - 2) = 3 + 2( x - 2) +  {(x - 2)}^{2}  = 3 + 2x - 4 +  {x}^{2}  - 4x + 4 =  {x}^{2}  - 2x + 3 \\  {x}^{2}  + 6x + 11 =  {x}^{2}  - 2x + 3 + 4 \\  {x}^{2}  -  {x}^{2}  + 6x + 2x + 11 - 3 - 4 = 0 \\ 8x + 4 = 0 \\ 8x =  - 4 \\ x =  -  \frac{1}{2}
Похожие вопросы